2022
DOI: 10.1007/s10120-022-01308-7
|View full text |Cite
|
Sign up to set email alerts
|

The combination of gene hyperamplification and PD-L1 expression as a biomarker for the clinical benefit of tislelizumab in gastric/gastroesophageal junction adenocarcinoma

Abstract: Background In solid tumor Phase 1/2 trials (NCT02407990; NCT04068519), tislelizumab demonstrated clinical benefit, including in advanced gastroesophageal adenocarcinoma (GEA). However, the majority of patients with GEA did not respond, highlighting the need to understand mechanisms of resistance and identify predictive biomarkers for response. Methods All tislelizumab-treated patients with GEA from the Phase 1/2 trials were included (N = 105). Programmed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Subsequently, 268 eligible studies were subjected to a full‐text review for further screening. Finally, 11 publications between 2018 and 2022 were included in the analysis 20,24–33 . The flowchart depicting the process of search and identification of studies is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, 268 eligible studies were subjected to a full‐text review for further screening. Finally, 11 publications between 2018 and 2022 were included in the analysis 20,24–33 . The flowchart depicting the process of search and identification of studies is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 11 publications between 2018 and 2022 were included in the analysis. 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 The flowchart depicting the process of search and identification of studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, the KEYNOTE-059 trial showed that, in metastatic GC or gastroesophageal junction cancer, the e cacy (ORR: 15.5% vs.6.4%) and the median duration of response (16.3 vs. 8.4 months) of patients with positive PD-L1 expression was far better than that of patients with negative PD-L1 expression [41]. Likewise, several studies have demonstrated that PD-L1 expression alone, or with other factors, is positively associated with the clinical bene ts of PD-1/PD-L1 inhibitors [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a positive correlation between TMB-H and GC incidence has been reported in meta-analyses, evidence also suggests that patients with high PD-L1 expression and TMB-H derive favorable survival benefits from ICIs ( 26 ). Meanwhile, it was reported in a study that PD-L1 positivity, Interferon-gamma (IFN-γ)-related gene signature, and TMB-H were positively associated with the clinical benefit of tislelizumab in advanced GEAC ( 27 ). It is uncertain whether this is a coincidence, but it is reasonable to speculate that patients with MSI-H/dMMR, TMB-H, and positive PD-L1 expression have better sensitivity to tislelizumab.…”
Section: Discussionmentioning
confidence: 99%
“…benefits from ICIs (26). Meanwhile, it was reported in a study that PD-L1 positivity, Interferon-gamma (IFN-g)-related gene signature, and TMB-H were positively associated with the clinical benefit of tislelizumab in advanced GEAC (27).…”
Section: A B Cmentioning
confidence: 99%